The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1177/1045389x16657204
|View full text |Cite
|
Sign up to set email alerts
|

Equi-biaxial fatigue behaviour of magnetorheological elastomers in magnetic fields

Abstract: The equi-biaxial fatigue behaviour of silicone-based magnetorheological elastomers in external magnetic fields was studied. Wöhler curves relating fatigue life to stress amplitude and dynamic stored energy for magnetorheological elastomers with a range of magnetic particle contents were derived. It was found that the fatigue life of magnetorheological elastomers in magnetic fields was higher than that without magnetic fields. Under constant stress amplitude conditions, the presence of magnetic fields resulted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Generally, the matrix should be highly elastic to allow the rearrangement of the particles under a magnetic field, and thereby to enhance the magnetic field induced mechanical properties of MREs. Consequently, silicone rubber and polyurethane, both with high elasticity, have been widely used as the matrix materials to fabricate various MRE composites [20][21][22]. In order to meet the likely requirement for mechanical strength in practical engineering applications, natural rubber, styrene-butadiene rubber and various polymer blends have also been used to fabricate MREs with improved mechanical properties [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the matrix should be highly elastic to allow the rearrangement of the particles under a magnetic field, and thereby to enhance the magnetic field induced mechanical properties of MREs. Consequently, silicone rubber and polyurethane, both with high elasticity, have been widely used as the matrix materials to fabricate various MRE composites [20][21][22]. In order to meet the likely requirement for mechanical strength in practical engineering applications, natural rubber, styrene-butadiene rubber and various polymer blends have also been used to fabricate MREs with improved mechanical properties [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…The images provided by the scanning electron microscopy (SEM) of the internal surface of the MRE indicated the collapse of this surface in the presence of a repetitive magnetic field. Zhou et al 15 studied the equi-biaxial fatigue behavior of MREs by using the bubble inflation method in the presence of an external magnetic field and provided a fatigue theory based on maximum stress and strain energy density methods for the determination of fatigue life of MREs. The results presented in the form of Wohler curves, and it was found that the elastomer's fatigue life is greater with an external magnetic field than without an external magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…Several works in technical literature (Li, 2013; Popp et al, 2009) are devoted to assess the MREs properties, especially as a function of the shear rate, focusing mainly on cyclic tests but scarce information is provided about their behavior up to failure, therefore the aim of this paper is to provide further information about the shear properties of MREs up to failure, since this important feature helps in the MREs based devices design. Only few works tackles the fatigue properties (Calabrò, 2011; Zhou, 2016; Zhou et al, 2017) mostly in biaxial condition while it is difficult to find information on the ultimate shear strength of MRE. This paper therefore investigates a MRE made from a silicone-elastomeric matrix, a combination already studied in literature, (Bellelli and Spaggiari, 2019; Choi et al, 2018), by considering several weight fractions, the applied magnetic field and the isotropicity of the material, by testing it dynamically at several shear rates and also up to failure, in order to estimate the effect of the variables on the material performance.…”
Section: Introductionmentioning
confidence: 99%